Comprehensive Review of Epidemiological Studies and Their Role in Public Health - Abkari, Sultan Ali Yahya; Ghazwani, Hussain Wajaan Hussain; Khudhayr, Yahya Mohasen Ali; Shabi, Ahmed Ali Ahmed; Aljabri, Faisal Hammad Oweidh; khayrat, Ahmed Nasser Mohammed; Khormi, Abdulrahman Ahmed Ebrahim; Mobarki, Ibrahim Abdullah Nasser; daghriri, Mohammed Ahmmed Hassan; gisi, Taher abdullah mohmmed (Journal of Ecohumanism, 2024)
Epidemiology is fundamental to public health, given its invaluable information concerning the pattern, causes, and disease prevention among the population. This review aims to identify and discuss major epidemiological studies that have informed public health policies, interventions, and global health. It reviews different study methods, including cross-sectional, cohort, case-control, and clinical trials, to illustrate their value in identifying disease trends and factors. Also, the review explores how epidemiology influences disease prevention, health promotion, and the formulation of health policies. Biases, ethical issues, and resource limitations in epidemiological research are also addressed. Thus, this systematic review underlines epidemiological data's roles in public health, emphasizing the suggestions for enhancing the designs, conducts, and utilization of other related research.